2017
DOI: 10.3382/ps/pew212
|View full text |Cite
|
Sign up to set email alerts
|

Dietary non-phytate phosphorus requirement of broilers fed a conventional corn-soybean meal diet from 1 to 21 d of age

Abstract: An experiment was conducted to investigate the effect of dietary non-phytate phosphorus (NPP) level on growth performance, bone characteristics and phosphorus metabolism-related gene expressions, so as to evaluate the dietary NPP requirement of broiler chicks fed a conventional corn-soybean meal diet from 1 to 21 d of age. A total of 540 day-old Arbor Acres male chicks were randomly allocated to one of nine treatments with six replicate cages of 10 birds per cage in a completely randomized design, and fed a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 52 publications
7
42
0
Order By: Relevance
“…The sample size calculation was performed using software PASS 13 (NCSS, LLC). In our previous study (17) , the means of duodenal NaPi-IIb mRNA expression levels for moderately restricted and normal NPP level treatments were 2•32 and 1•03 with a pooled SD of 0•63. On the basis of the same effect size, five replicates per treatment are needed to achieve 80 % power using a two-sided two-sample t test at a significance level of 0•05.…”
Section: Statistical Analysesmentioning
confidence: 81%
“…The sample size calculation was performed using software PASS 13 (NCSS, LLC). In our previous study (17) , the means of duodenal NaPi-IIb mRNA expression levels for moderately restricted and normal NPP level treatments were 2•32 and 1•03 with a pooled SD of 0•63. On the basis of the same effect size, five replicates per treatment are needed to achieve 80 % power using a two-sided two-sample t test at a significance level of 0•05.…”
Section: Statistical Analysesmentioning
confidence: 81%
“…Many studies demonstrated that the bone development parameters, such as tibia BMD, BBS, and ash content of broilers, were susceptible to dietary Ca or P level ( Williams et al., 2000a , Rama Rao et al., 2003 , Liu et al., 2017 ). Results from the present study showed that the Ca- or P-deficient diets negatively affected the tibia BMD, BBS, and ash content of broilers.…”
Section: Discussionmentioning
confidence: 99%
“…The frozen tibiae were thawed at room temperature for 2 h and then stripped of all soft tissues. The tibia BMD ( Liu et al., 2017 , Jing et al., 2018 ) was determined by dual-energy X-ray absorptiometry. The tibia BBS was determined by a 3-point bending test (HDP/3PB Texture Analyzers, West Sussex, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The right tibiae was cleaned and dried for determination of tibia weight and tibia breaking strength [22]. The bones were then ashed in a mu e furnace at 550 °C for 16 h [19]. After that, the tibia P content was measured using the vanadate-molybdate method.…”
Section: Experimental Designmentioning
confidence: 99%